Determining the Components of the Policy Evaluation Model for Recruiting and Utilizing Public Capacity in Iran’s Administrative System - Bashiri, Abdolreza; Mohammadian Saravi, Mohsen; Chegin, Meysam (Management Strategies and Engineering Sciences, 2025)
The present study was conducted to determine the components of the policy evaluation model for recruiting and utilizing public capacity in Iran’s administrative system. This study is applied in terms of its objective and qualitative in terms of data type, employing a systematic literature review and thematic analysis. The study population consisted of general directors, deputies, and managers of non-governmental organizations (NGOs), as well as academic experts in policymaking from the southern provinces of Iran (Khuzestan, Bushehr, and Hormozgan). The sample size for the thematic analysis included 16 interviewees, selected through purposive sampling based on the principle of saturation. Data collection tools included library documents and semi-structured interviews with experts. To ensure validity, expert opinions were utilized, and to assess reliability, inter-coder agreement was applied, indicating that the instruments were both valid and reliable. Data analysis was conducted using thematic analysis (basic, organizing, and overarching themes) with Maxqda2020 software. Findings revealed that the components constituting the policy evaluation model for recruiting and utilizing public capacity in Iran’s administrative system include transparency and information dissemination (publication of information, free access to information, transparency in criteria and methods, and emphasis on transparency in policies), justice and equality (equal access to resources, creating equal opportunities for public participation in decision-making processes, and equality in advancement opportunities), skill identification and selection (identifying organizational needs, assessing individual skills, and recognizing future leaders), research and development (needs and problem analysis, research and development planning, basic and applied research, and collaboration with universities and research centers), participation and partnership (establishing a participatory culture, partnerships with local communities and the public, cooperation with organizations and institutions, and partnership opportunities in the evaluation process), economic justification evaluation (cost analysis, benefit analysis, risk and uncertainty analysis, and social justification analysis), compliance evaluation with laws (alignment with laws and regulations, ensuring rights protection and guarantees), and regulatory framework and innovation culture (values and beliefs, attitudes and behaviors, and enthusiasm for risk-taking and learning).